INFLUENCE OF SEED PRIMING TREATMENTS ON GERMINATION AND SEEDLING VIGOUR OF CUSTARD APPLE ( ARD APPLE (ANNONA SQUAMOSA L.) CV. LOCAL - PARMAR, R. K.; M. J, PATEL; AND T. TSOMU, R. M. THAKKAR (The Bioscan, 2016)
An investigation was conducted to study the influence of seed priming treatments on germination and seedling vigour of custard apple. The treatments comprised of different concentrations of chemicals (GA3 @ 100 and 200 mgL-1, KNO3 @ 1 and 2%, Thiourea @ 500 and 1000 mgl-1), fresh cow dung and urine slurry (1:2 ratio) and hot water treatment. Soaking the seed in GA3 @ 200 mgL-1 for 12 hours recorded the minimum days taken to germinate (24.00 days), maximum germination percentage (63.99 %) and height of seedling (64.87 cm), shoot length (45.90 cm), root length (20.00 cm), fresh and dry weight of seedling (7.27 g and 4.36 g), stem girth (0.73 cm), relative growth rate (0.026 g/day), vigour index-I and II (0.99 and 14.68) at 120 days of sowing. From the above values, GA3 @ 200 mgL-1 for 12 hourswas found best seed priming treatment for maximum germination and seedling growth of custard apple.